(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is devoted to the issue of individual author’s “language picture of the world” on the material of poetic speech of M. Vingranovsky. The thematic field “Space” in which the author presents a unique view to their homeland. The complex lexical analysis on the material of the collection of poems “On the silver bank” reveales that the thematic field is presented in ten lexical-semantic groups: “Place names”, “Hydronyms” “The names of countries”, “Exotic geographical names”, “Landscape”, “Soil”, “Plants”, “Water space”, “Sky, space”, “Building”. The individual writing style of Ukrainian poet presents a unique world with only his realities based, of course, on the national language paradigm. M. Vingranovsky presents all Ukraine. Cities cover the state space from the West (Lviv as city of love which is associated for the artist with I. Franko and Prince Daniel Galician) to the East (Donetsk region), from the North (Kyiv) to South (Odessa), Center (Kaniv, a famed city for everyone due to the Ukrainian T. Shevchenko, Veseli Bokovenki, Kirovohrad region), the Crimea (Sevastopol) and Krivyi Rih (iron heart of the country). The poet creates an almost cinematic image of a united integrated country – Motherland, Ukraine, Ukrainian World to his own mind shared by the Ukrainians. The artist delights landscapes of fields, steppes, valleys, grasslands, deserts, ravines. Elements of industrial landscape – career, which is also a sign of the southern regions – are of great interest. These lands unite ways, paths not only in geographical sense, but also in the sense of life styles.